A Pragmatic Analysis Of Directive Utterances In Oh, Brother! Comic Strip - Gunanto, Basuki Okto; , Drs. H. Maryadi, M.A; , Dra. Siti Zuhriah Ariatmi, M. Hum (2013)
This research focuses describing the intention of directive utterances based on illocutionary act and FTA/ politeness strategy used in Oh, Brother! comic strip. This research aimed at 1) describing the directive utterances based on illocutionary act, 2) describing the FTA / Politeness Strategy in the Oh, Brother! comic strip. This research applies descriptive qualitative method. The data are utterances that are containing directive utterances in 25 serials of Oh, Brother! comic strip. In collecting the data, the writer uses a documentation method by reading, classifying, underlining and coding the data. The study shows that: 1) the category of directive utterances based on illocutionary act used in Oh, Brother! comic strip are 11 (27,5%) data of the directive commanding category, 4 (10%) data of the directive suggesting category, 21 (52.5%) data of the directive requesting category and 4 (10%) data of the directive warning category. And the last is 2) the FTA / Politeness Strategy, the writer finds 18 (45%) data of the politeness bald on record strategy, 3 (7,5%) data of the politeness off-record strategy, 14 (35%) data of the positive politeness strategy, and 5 (12.5%) data of the negative politeness strategy.